Semantic peculiarities of the verbs in the syntactic constructions used to describe emotional states in Spanish - Natalia A. Mijeeva (Ибероамериканские тетради, 2016)
This article is dedicated to investigation of the syntactic constructions describing emotional state of a person in Spanish: constructions with verba sentiendi, constructions with change of the empathy, causative constructions. These constructions have a determinate semantic structure which includes a predicate name of emotion and a verb. Diﬀerent classiﬁcations of the verbs used in the above mentioned syntactic constructions are expounded and their semantic peculiarities are analysed in the article.